Quality assurance multi-component environments moved belt conveyors energy saving pulsed magnetic extraction - О. S. Parsentev; T. A. Musaev (Омский научный вестник)
The article presents theoretical and practical aspects of improving the designs of existing separation subsystems using the results of historical and patent information studies used to detect and extract ferromagnetic bodies in a flow of multicomponent non-magnetic lumpy, granular and finely divided and friable media. A new energysaving technological approach proposed with the effect of synchronously improving the performance of the transport and technological system and reducing the cost and energy costs during its operation, in particular in the material flow separation subsystem. A subsystem for the separation-detection of metal fragments in a non-magnetic granular medium proposed for the development of signaling and current control devices in extracting windings. To increase the extraction capacity during the purification of non-magnetic granular media, a design of a combined iron separator proposed. Mathematical modeling of the operation of the electromagnetic system of the combined iron separator of the transport system is carried out, on the basis of which a mathematical model of the magnetic field in its working area is proposed, which makes it possible to determine the extracting force from the windings with and current. An experimental verification of the results of theoretical studies of pulsed magnetic extraction of ferromagnetic bodies from a granular medium is carried out.